Patient Chief Complaint and Otolaryngology Referral Rationale: Discordance and Opportunities for Quality Improvement. (October 2022) - Mann, Scott E.; White, Shelby; Officer, Laurel C.; Ramos, Laylaa; Hirsch, Scott; Ferril, Geoffrey R.
Objective: As medical systems focus on patient satisfaction as an important care outcome, specialty clinics are tasked with continued improvement of patients' experience. When patient expectations for a consultation differ from that of the specialty provider, dissatisfaction with the experience can occur. One source of differing expectations is discordance between the patient's chief complaint and the clinical rationale for the consultation as requested by the referring provider. We sought to better understand when this discordance occurs, as well as factors contributing to this disorientation of patient and provider expectations in a safety net otolaryngology practice. Methods: A retrospective observational study was performed and records were examined from new patient consultations. Patient questionnaires, including self-reported chief concerns, were compared with the electronic referral documentation. A difference between the patient's Chief Complaint (CC) and Referral Reason (RR) was defined as CC-RR Discordance. Medical records, pre-consultation patient communication, and scheduling data were also reviewed to evaluate contributing factors. Results: Of the 1155 consultations examined, 952 were included in the analysis. A CC-RR Discordance was found in 175 (18.4%) of new-patient encounters, including 117 (12.3%) that were unable to articulate a CC (unsure of the reason for the appointment), and 58 (6.1%) that stated a CC that was different than the RR. The rate of CC-RR Discordance was higher in patients with female sex ( P  < .05), older age ( P  < .001), and longer time intervals between referral and appointment ( P  < .05). Lack of communication with the patient (instructions or referral notification) by the referring provider was not associated with CC-RR Discordance. Conclusions: Discordance between patient CC and the rationale for a consultation is common in this safety-net otolaryngology practice and may be an important source of patient dissatisfaction. Future opportunities for quality improvement include pre-consultation communication between the specialist and the patient and reducing time intervals between referral and appointment.